The transactivator gene of human T-cell leukemia virus type I is more variable within and between healthy carriers than patients with tropical spastic paraparesis. - Niewiesk, S (1994)
Human T-cell leukemia virus type I (HTLV-1) causes T-cell leukemia and tropical spastic paraparesis (TSP) in a minority of infected people, whereas the majority remain healthy. No association between a particular HTLV-I sequence and disease manifestation has been found in previous studies. We studied here the sequence variability of the gene for the HTLV-I Tax protein, which is the dominant target antigen of the very strong cytotoxic T-lymphocyte response to the virus. In HTLV-I infection, the intraisolate nucleotide variability is much greater than the variability between isolates. The predicted protein sequence of Tax was significantly more variable in the healthy seropositive individuals' provirus than in those of the patients with TSP. Thus, tax sequence heterogeneity, rather than the presence of particular sequences, distinguishes healthy HTLV-I-seropositive individuals from patients with TSP.